Avaliação do Programa Institucional de Bolsa de Iniciação à Docência - PIBID no Instituto Federal do Ceará – Campus Acaraú - Martins, Rosenete Pereira (2020)
The main objective of this research was to evaluate the institutional teaching initiation scholarship program - (Pibid) and its contributions to the training of undergraduate students at IFCE courses - Campus Acaraú. In this sense, it was decided to use Pibid as the object of study, as it is a program whose objectives are to encourage the training of teachers for basic education. The research adopted as an evaluative perspective the Assessment in Depth (RODRIGUES, 2008), where the analytical dimensions (context, content, policy trajectory, and temporal and territorial spectrum) were used. The approach was qualitative because this method offered greater interaction between the researcher and the research subjects. As for the objectives, the research had an exploratory and descriptive character. In the field, semi-structured interviews were used as a data collection instrument, which was applied to both area coordinators and program participants, in addition to this procedure, documentary research was used, which aimed to understand the nuances of structuring PIBID. In order to substantiate the study, the categories of analysis were adopted as a basis for support: neodevelopment; human capital theory; teacher training and the precariousness of teaching work. The results obtained showed what is deposited in the official records, the respondents' manifestations expressed a feeling of satisfaction for having been part of the program, shown through the actions experienced. In general, reports from both students and managers indicate that Pibid is important, not only because of the student's formative contributions but also because of the pedagogical contribution to basic education, since students take different methodological proposals to schools, ranging from against traditional teaching methods worked daily in public schools in the municipality. The evaluative perspective adopted in this dissertation revealed that PIBID is an important policy of incentive and qualification for teacher training, as it promotes the insertion of students in the school environment, which is the place for practical learning and for promoting the professional development of future teachers.